The impact of the Juntos conditional cash transfer programme in Peru on nutritional and cognitive outcomes: does the age of exposure matter? - Sánchez, Alan (2016)
In this study we revisit the impact of conditional cash transfers (CCTs) on child development, with an emphasis on the role of the age of exposure. We use longitudinal data from a unique paired-siblings sample of Peruvian children (the Young Lives study) to evaluate whether Juntos, a large-scale CCT implemented in Peru since 2005, has a greater effect on children who benefited from the programme during the first three years of life compared with its impact on those children who benefited between the ages of 5 and 7. To deal with programme selection we apply child fixed-effects methods. We find that exposure to the programme leads to a reduction in severe stunting and an improvement in height-for-age – but only for those exposed during the first three years of life. This result suggests that timing of exposure matters. However, no cognitive impact (as measured by a vocabulary-development test) is detected for either group.